MXene-SS / SF composite material and preparation method and application thereof

By distributing the laminated nanocomposite membrane and silk protein structure on the surface of MXene nanosheets, MXene-SS/SF composite materials were prepared, which solved the toxicity problems of MXene easy oxidation and traditional hydrogel materials, and achieved a humidity sensing material with high conductivity, hydrophilicity and stability.

CN119823582AActive Publication Date: 2025-04-15NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510105255.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

MXene is prone to oxidation in a water-oxygen environment, resulting in unstable sensing. In traditional hydrogel materials, there are problems such as solvent evaporation, resulting in reduced conductivity and acrylamide monomers having certain toxicity.

Method used

Using MXene-SS/SF composite material, a laminated nanocomposite film with continuous folds distributed on the surface of MXene nanosheets is combined with the β-sheet secondary structure of silk proteins to form the long edge of nanofibers, improve the oxidation stability, and a composite material with conductive and hydrophilicity is prepared by self-assembly method.

Benefits of technology

The significant electrical conductivity, good hydrophilicity and good oxidative stability of MXene composite materials are achieved, the sensitivity and response performance of humidity detection are improved, and the material safety is higher.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823582A_ABST
    Figure CN119823582A_ABST
Patent Text Reader

Abstract

The invention discloses an MXene-SS / SF composite material and a preparation method and application thereof.The MXene-SS / SF composite material is a laminated nano composite film with continuous folds distributed on the surface, the mass ratio of SS to SF in the MXene-SS / SF composite material is 1: 2, SS is sericin separated after silk is alkalized, SF is silk fibroin, and the composition structure of MXene is Ti3C2Tx; the MXene-SS / SF composite material can be applied to physical detection as a sensing humidity-sensitive layer. The MXene-SS / SF composite material disclosed by the invention has a continuous electron transmission channel, relatively high porosity and relatively large specific surface area under the support of structural protein, more active sites are endowed by functional groups existing on the surface, and the MXene-SS / SF composite material has remarkable conductivity and good hydrophilicity; the sensor constructed by the MXene-SS / SF composite material is high in humidity detection sensitivity and wide in detection limit, has excellent response and recovery performance in the aspect of humidity detection, and has huge application potential in the field needing rapid humidity detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material and a preparation method and application thereof, in particular to a MXene-SS / SF composite material and a preparation method and application thereof. Background Art

[0002] In contactless human-computer interaction, as well as in public safety, precision medicine, and industrial production, it is very important to design sensing hygroscopic materials with high sensitivity, wide detection limit, and high responsiveness to detect humidity.

[0003] As a new member of inorganic 2D materials, MXene has become an excellent candidate material in the field of smart sensing due to its unique structural characteristics, hydrophilicity, high specific surface area, metallic conductivity and other physical and chemical properties. However, MXene is easily oxidized in water and oxygen environments, resulting in unstable sensing, which cannot be ignored when designing composite materials for practical humidity sensing applications. Biomass materials have been favored by more and more researchers in different fields in recent years due to their environmental friendliness, wide sources, renewability and relatively low prices. Two-dimensional materials introduce natural biopolymers to improve material functions.

[0004] For example, Fe3O4-COOH nanoparticles loaded on the MXene surface effectively alleviated the restacking of MXene nanosheets in aqueous solution, and generated polyacrylamide (PAAm) hydrogels with good stability without using any initiator. Fe3O4-COOH@MXene nanosheets acted as conductive fillers, crosslinkers, and catalysts for rapid gelation of hydrogels, making the obtained FM@SF-PAAM hybrid hydrogels have good conductivity (6.44·10 -2 S·m -1 ). However, it has certain limitations: although the strong connection of the polymer chains formed during the cross-linking process of the hydrogel makes them insoluble in water, the presence of hydrophilic functional groups allows them to absorb a large amount of solvent, but due to exposure to air, the solvent will evaporate to a certain extent, and the reduction of water content in the hydrogel structure will affect its conductivity. In addition, acrylamide monomers have certain toxicity, and improper handling may cause poisoning. Summary of the invention

[0005] The purpose of the invention is to provide a MXene-SS / SF composite material and a preparation method and application thereof, which can realize a composite material with significant conductivity, good hydrophilicity and good oxidation stability.

[0006] Technical solution: The MXene-SS / SF composite material described in the present invention is a laminated nanocomposite film with continuous wrinkles distributed on the surface, and the mass ratio of SS to SF in the MXene-SS / SF composite material is 1:2.

[0007] As a further limitation of the composite material of the present invention, the thickness of the MXene-SS / SF composite material is less than 10 nm.

[0008] As a further definition scheme of the composite material of the present invention, the nitrogen-containing silk protein in the MXene-SS / SF composite material is uniformly distributed along the MXene layer, and the silk protein β-folded secondary organization extends through the edge of the MXene layer and forms the long edge of the nanofibril around a single MXene layer.

[0009] The present invention also provides a method for preparing a MXene-SS / SF composite material, which is used to prepare a MXene-SS / SF composite material, comprising the following steps:

[0010] Step 1, preparing a MXene nanosheet dispersion;

[0011] Step 2: Add SS solution and SF solution to the MXene nanosheet dispersion to obtain a two-dimensional layered MXene-SS / SF composite material through mixing and self-assembly.

[0012] As a further limitation of the preparation method of the present invention, in step 1, the specific steps of preparing the MXene nanosheet dispersion are:

[0013] Step 1.1, uniformly mixing titanium aluminum carbide and lithium fluoride according to a set mass ratio;

[0014] Step 1.2, after being mixed evenly, adding the mixture into the hydrochloric acid in the reaction kettle, and etching at high temperature in the hydrochloric acid environment;

[0015] Step 1.3, obtaining MXene nanosheets after washing and centrifugation;

[0016] Step 1.4, ultrasonically disperse the MXene nanosheets in ultrapure water to obtain a MXene nanosheet dispersion.

[0017] As a further limitation of the preparation method of the present invention, in step 1.1, the mass ratio of titanium aluminum carbide and lithium fluoride is set to 1:1.6.

[0018] As a further limitation of the preparation method of the present invention, in step 1.2, the concentration of hydrochloric acid is 12 mol / L, the etching time is 12 to 24 h, the heating temperature in the reactor is 40° C. to 50° C., and the stirring speed is 450 to 550 r / min.

[0019] As a further limitation of the preparation method of the present invention, in step 1.4, the mass ratio of MXene nanosheets to ultrapure water is 1:100, and the ultrasonic dispersion time is 1 to 2 hours.

[0020] As a further limiting scheme of the preparation method of the present invention, in step 2, when SS solution and SF solution are added to the MXene nanosheet dispersion, the mass parameter relationship between the MXene nanosheet dispersion, the SS solution and the SF solution is 7:1:2; during mixed self-assembly, after stirring at room temperature for 4 to 5 hours, ultrasonication for 1 to 2 hours is performed to obtain a MXene-SS / SF composite material with a total solute concentration of 10 mg / mL.

[0021] The present invention also provides an application of a MXene-SS / SF composite material as a humidity sensing layer in physical detection.

[0022] Compared with the prior art, the present invention has the following beneficial effects: the MXene-SS / SF composite material of the present invention is a layered 2D material of several nanometers thick tightly encapsulated by a biopolymer nanoscale coating; the composite film has a continuous electron transmission channel, a high porosity and a large specific surface area under the support of structural proteins; the functional groups on the surface give it more active sites, thereby having significant conductivity and good hydrophilicity; in addition, the silk protein-encapsulated MXene nanosheets show nanofibril edges around the sheet layer, and have better oxidative stability than pure MXene; the sensor constructed by the MXene-SS / SF composite material has high sensitivity to humidity detection, a wide detection limit, and excellent response and recovery performance in humidity detection, and therefore has great application potential in fields requiring rapid humidity detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope image of the MXene-SS / SF composite material of the present invention;

[0024] Figure 2 is a scanning electron microscope cross-sectional view of the MXene-SS / SF composite material of the present invention;

[0025] Figure 3 is an X-ray energy spectrum diagram of the MXene-SS / SF composite material of the present invention; wherein, O element, Ti element, N element, and C element are included;

[0026] Figure 4 It is the continuous dynamic humidity response of the LIG sensor modified by the MXene-SS / SF composite material with different mass ratios of the present invention to 6% RH;

[0027] Figure 5 It is the continuous dynamic humidity response of the humidity sensor modified by the MXene-SS / SF (1:2) composite material of the present invention in the range of relative humidity 6% to 98%;

[0028] Figure 6This is the real-time hysteresis characteristic curve of the humidity sensor modified by the MXene-SS / SF (1:2) composite material of the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail below with reference to the accompanying drawings, but the protection scope of the present invention is not limited to the embodiments.

[0030] like Figure 1 As shown, the MXene-SS / SF composite material disclosed in the present invention is a laminated nanocomposite film with continuous wrinkles distributed on the surface. The mass ratio of SS to SF in the MXene-SS / SF composite material is 1:2. MXene is a two-dimensional sheet nanomaterial. SS is sericin separated from silk after alkalization. SF is silk fibroin. The composition structure of MXene is Ti3C2T x .

[0031] As a further limitation of the composite material of the present invention, the thickness of the MXene-SS / SF composite material is less than 10 nm.

[0032] As a further limitation of the composite material of the present invention, the C, O, Ti, and N elements in the MXene-SS / SF composite material are distributed in a lamellar morphology, that is, the nitrogen-containing silk protein is evenly distributed with the MXene lamellar layer, so that the MXene-SS / SF composite material exhibits a microscopic morphology of a continuous and complete conductive network film, and the silk protein β-folded secondary organization extends through the edge of the MXene nanosheet layer and forms a long edge of the nanofibril around a single MXene lamellar layer, thereby improving its oxidative stability.

[0033] The present invention also provides a method for preparing a MXene-SS / SF composite material, which is used to prepare a MXene-SS / SF composite material, comprising the following steps:

[0034] Step 1, preparing a MXene nanosheet dispersion;

[0035] Step 2: Add SS solution and SF solution to the MXene nanosheet dispersion to obtain a two-dimensional layered MXene-SS / SF composite material through mixing and self-assembly.

[0036] As a further limitation of the preparation method of the present invention, in step 1, the specific steps of preparing the MXene nanosheet dispersion are:

[0037] Step 1.1, uniformly mixing titanium aluminum carbide and lithium fluoride according to a set mass ratio;

[0038] Step 1.2, after being mixed evenly, adding the mixture into the hydrochloric acid in the reaction kettle, and etching at high temperature in the hydrochloric acid environment;

[0039] Step 1.3, obtaining MXene nanosheets after washing and centrifugation;

[0040] Step 1.4, ultrasonically disperse the MXene nanosheets in ultrapure water to obtain a MXene nanosheet dispersion, for example, ultrasonically disperse 35 mg of MXene nanosheets in 5 ml of ultrapure water.

[0041] As a further limitation of the preparation method of the present invention, in step 1.1, the mass ratio of titanium aluminum carbide and lithium fluoride is set to 1:1.6.

[0042] As a further limiting scheme of the preparation method of the present invention, in step 1.2, the concentration of hydrochloric acid is 12 mol / L, the etching time is 12 to 24 hours, the optimal time is 24 hours, the heating temperature in the reactor is 40°C to 50°C, 42°C is the optimal etching temperature, and the stirring speed is 450 to 550 r / min, preferably 500 r / min.

[0043] As a further limiting scheme of the preparation method of the present invention, in step 1.3, when washing, washing with dilute hydrochloric acid is performed 2 to 4 times, and washing with deionized water is performed 5 to 7 times until the pH is neutral; when centrifuging, after ultrasonication for 1 hour under ice water bath conditions, centrifugation is performed at a speed of 3500r / min for 1 hour.

[0044] As a further limitation of the preparation method of the present invention, in step 1.4, the mass ratio of MXene nanosheets to ultrapure water is 1:100, and the ultrasonic dispersion time is 1 to 2 hours, and the ultrasonic effect is better for 2 hours.

[0045] As a further limiting scheme of the preparation method of the present invention, in step 2, when SS solution and SF solution are added to the MXene nanosheet dispersion, the mass parameter relationship between the MXene nanosheet dispersion, the SS solution and the SF solution is 7:1:2; during mixed self-assembly, after stirring at room temperature for 4 to 5 hours, ultrasonically applied for 1 to 2 hours, preferably stirred for 5 hours and then ultrasonically applied for 2 hours, to obtain a MXene-SS / SF composite material with a total solute concentration of 10 mg / mL.

[0046] The present invention also provides an application of a MXene-SS / SF composite material as a sensing humidity sensitive layer in physical detection. Sericin (SS) forms a green adhesive and dispersant through strong non-covalent interactions. The secondary structure of silk fibroin (SF) has a humidity-sensitive structural change. It is used as an interlayer regulator of MXene nanosheets for intercalation regulation, so that the interior of the MXene sheet has a continuous electron transmission channel, a high porosity and a large specific surface area under the support of the fiber, and has the advantages of high conductivity and good mechanical flexibility. Therefore, it can be used as a sensing humidity sensitive layer in physical detection. For example, a flexible humidity sensor is developed on a polyimide (PI) substrate using a MXene-SS / SF composite material as a humidity sensitive material and laser-induced graphene (LIG) as a bottom electrode. Under different relative humidity conditions (RH 6% to 97%), the humidity sensor is tested for sensing performance by using a chronoamperometric method (Amperometric it Curve, it) with a voltage of 1V, and the relationship between the current of the sensing system and time under different RH environmental conditions is recorded.

[0047] When making sensors from MXene-SS / SF composite materials, in an air environment, a CO2 laser was used to directly write a patterned graphene electrode on a polyimide (PI) film using the optimal laser parameter configuration of 17W power and 130mm / s scanning speed. Then, a pipette was used to transfer 100μL of the prepared MXene-SS / SF composite materials at six different mass ratios and evenly drop them on the surface of the LIG interdigital electrode. The humidity sensor was then dried at room temperature to remove the solvent to obtain a humidity sensor.

[0048] Example 1

[0049] When preparing MXene-SS / SF composites with different ratios:

[0050] First, the nanomaterial MXene was synthesized using the fluorine-containing molten salt etching method;

[0051] 1.6g lithium fluoride and 1g titanium aluminum carbide were added to 20ml of 12mol concentrated hydrochloric acid, and the etching time was 24h; the heating temperature in the reactor was 42°C, the stirring speed was 500r / min, and then MXene nanosheets were obtained after washing and centrifugation;

[0052] 210 mg of MXene nanosheets were ultrasonically dispersed in 30 mL of water and divided into 6 equal portions for the next step. SS-SF solutions with a mass ratio of SS to SF of a:b (3:1, 2:1, 1:1, 0:1, 1:0, and 1:3) were then prepared. The SS-SF solutions with different mass ratios were then added to each equal portion of the MXene nanosheet dispersion.

[0053] Finally, the mixture was stirred at room temperature for 5 h and ultrasonicated for 2 h to obtain a MXene-SS / SF composite material with a total solute concentration of 10 mg / mL.

[0054] When constructing humidity sensors using MXene-SS / SF composite materials:

[0055] First, in an air environment, a CO2 laser was used to directly write a graphene electrode on a polyimide (PI) film using the optimal laser parameter configuration of 17W power and 130mm / s scanning speed.

[0056] Then, 100 μL of the six prepared MXene-SS / SF composite materials with different mass ratios were respectively transferred with a pipette and evenly dropped on the surface of the LIG interdigital electrode. The mixture was dried at room temperature to remove the solvent and obtain six different humidity sensors.

[0057] Example 2

[0058] When preparing MXene-SS / SF (1:2) composite materials:

[0059] First, the nanomaterial MXene was synthesized using the fluorine-containing molten salt etching method;

[0060] 1.6g lithium fluoride and 1g titanium aluminum carbide were added to 20ml of 12mol concentrated hydrochloric acid, and the etching time was 24h; the heating temperature in the reactor was 42°C, the stirring speed was 500r / min, and then MXene nanosheets were obtained after washing and centrifugation;

[0061] Subsequently, 35 mg of MXene nanosheets were ultrasonically dispersed in 5 mL of water to prepare a MXene nanosheet dispersion, and then an SS-SF solution with a mass ratio of SS to SF of 1:2 was prepared. The SS-SF solution with a mass ratio of 1:2 was added to the MXene nanosheet dispersion, stirred at room temperature for 5 h, and then ultrasonicated for 2 h to obtain a MXene-SS / SF composite material with a total solute concentration of 10 mg / mL, as shown in FIG. Figure 1 , Figure 2 and Figure 3 shown.

[0062] from Figure 1 and Figure 2It can be seen that the biopolymer nanoscale coating tightly encapsulates a few nanometers thick layered 2D material, and the secondary structure of SF with humidity-sensitive structural changes can be used as a regulator between MXene nanosheets, while SS is used as a green adhesive and dispersant through strong non-covalent interactions. Supported by structural proteins, the composite membrane has continuous electron transport channels, high porosity and large specific surface area. The functional groups on the surface give it more active sites, thus having significant conductivity and good hydrophilicity. In addition, the nanofibril edges displayed by silk protein-encapsulated MXene nanosheets around the sheets have better oxidative stability. Figure 3 This is the EDS spectrum of the MXene-SS / SF (1:2) composite material. As shown in the figure, the C, O, Ti, and N elements are distributed in a lamellar morphology. This result further confirms that SS and SF are "soft armor" covering the surface of MXene, forming a complete and continuous conductive network. Therefore, it can be proved that the present invention successfully prepared the MXene-SS / SF composite material.

[0063] When constructing the MXene-SS / SF (1:2) humidity sensor:

[0064] In an air environment, a CO2 laser was used to directly write a graphene electrode on a polyimide (PI) film using the optimal laser parameter configuration of 17W power and 130mm / s scanning speed.

[0065] Then, 100 μL of the prepared MXene-SS / SF composite material with a mass ratio of SS:SF=1:2 was transferred with a pipette and evenly dropped on the surface of the LIG interdigital electrode, and dried at room temperature to remove the solvent to obtain a humidity sensor.

[0066] Example 3

[0067] When the MXene-SS / SF composite materials with different mass ratios obtained according to the methods of Example 1 and Example 2 are used as humidity-sensitive materials:

[0068] Polyimide (PI) film was used as a flexible substrate, and laser-induced graphene (LIG) was prepared as the bottom electrode using the optimal laser parameters of 17W power and 130mm / s scanning speed to prepare a humidity sensor based on a composite humidity-sensitive layer. Various saturated salt solutions were prepared as saturated salt standard humidity sources, including LiBr, LiCl, MgCl2, NaBr, NaCl, KCl and K2SO4. The sensor was exposed to the above different saturated salt solution environments. The chronoamperometric method (Amperometric it Curve, it) was used to apply a constant working voltage of 1V, and the response-recovery performance of each sensor was tested under different relative humidity conditions (RH 6%~97%). The relationship between the current of the sensing system and time under different RH environmental conditions was recorded to evaluate the humidity sensitivity of each composite film.

[0069] like Figure 4 As shown, it can be seen that under the same relative humidity conditions, the MXene-SS / SF composite material with a mass ratio of SS to SF of 1:2 exhibits higher sensitivity than composite materials with other mass ratios.

[0070] Example 4

[0071] The MXene-SS / SF (1:2) humidity-sensitive material obtained according to the method of Example 3 is used as the humidity-sensitive layer of the sensor, and a polyimide (PI) film is used as a flexible substrate. The laser-induced graphene (LIG) is prepared using the optimal laser parameters of 17W power and a scanning speed of 130mm / s as the bottom electrode to prepare a humidity sensor based on a composite humidity-sensitive layer; various saturated salt solutions are prepared as saturated salt standard humidity sources, including LiBr, LiCl, MgCl2, NaBr, NaCl, KCl and K2SO4; the sensor is exposed to the above-mentioned different saturated salt solution environments, and a chronoamperometric method (Amperometric it Curve, it) is used to apply a constant working voltage of 1V to perform a continuous dynamic humidity response test with RH values ​​varying from 6% to 98%. The performance of the MXene-SS / SF (1:2) humidity-sensitive sensing material for humidity monitoring is reflected by detecting the change in current response with humidity. The change in current response with relative humidity is shown in FIG. Figure 5 As shown in Figure 2, the hysteresis curve of the sensor under the condition of MXene-SS / SF (1:2) is as follows: Figure 6 shown.

[0072] The results show that if Figure 5 As shown in Figure 2, the current intensity decreases with increasing relative humidity and has good repeatability. Figure 6It can be found that the hysteresis curve obtained by linear fitting can find that there is a good linear relationship between the response current and the relative humidity conditions. After calculation, it is found that the sensor achieves low hysteresis, the hysteresis is less than 3.7%RH, and the larger hysteresis mainly occurs at 23%RH.

[0073] From the above, it can be seen that the sensor constructed with the MXene-SS / SF composite material with a mass ratio of SS to SF of 1:2 as a humidity-sensitive material has high humidity detection sensitivity, a wide detection limit, good stability, and excellent performance in humidity detection. Therefore, it has great application potential in fields that require rapid response to humidity.

[0074] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A MXene-SS / SF composite material, characterized in that: The MXene-SS / SF composite material is a laminated nanocomposite film with continuous wrinkles distributed on the surface. The mass ratio of SS to SF in the MXene-SS / SF composite material is 1:

2.

2. The MXene-SS / SF composite material according to claim 1, characterized in that The thickness of the MXene-SS / SF composite is less than 10 nm.

3. The MXene-SS / SF composite material according to claim 1, characterized in that The nitrogen-containing silk protein in the MXene-SS / SF composite is evenly distributed along the MXene sheets, and the β-folded secondary organization of the silk protein extends through the edge of the MXene sheets and forms the long edges of the nanofibrils around a single MXene sheet.

4. A method for preparing a MXene-SS / SF composite material, characterized in that: The method for preparing the MXene-SS / SF composite material according to any one of claims 1 to 3 comprises the following steps: Step 1, preparing a MXene nanosheet dispersion; Step 2: Add SS solution and SF solution to the MXene nanosheet dispersion to obtain a two-dimensional layered MXene-SS / SF composite material through mixing and self-assembly.

5. The method for preparing the MXene-SS / SF composite material according to claim 4, characterized in that: In step 1, the specific steps for preparing the MXene nanosheet dispersion are: Step 1.1, uniformly mixing titanium aluminum carbide and lithium fluoride according to a set mass ratio; Step 1.2, after being mixed evenly, adding the mixture into the hydrochloric acid in the reaction kettle, and etching at high temperature in the hydrochloric acid environment; Step 1.3, obtaining MXene nanosheets after washing and centrifugation; Step 1.4, ultrasonically disperse the MXene nanosheets in ultrapure water to obtain a MXene nanosheet dispersion.

6. The method for preparing the MXene-SS / SF composite material according to claim 5, characterized in that: In step 1.1, the mass ratio of titanium aluminum carbide and lithium fluoride is set to 1:1.

6.

7. The method for preparing the MXene-SS / SF composite material according to claim 5, characterized in that: In step 1.2, the concentration of hydrochloric acid is 12 mol / L, the etching time is 12 to 24 h, the heating temperature in the reactor is 40° C. to 50° C., and the stirring speed is 450 to 550 r / min.

8. The method for preparing the MXene-SS / SF composite material according to claim 1, characterized in that: In step 1.4, the mass ratio of MXene nanosheets to ultrapure water is 1:100, and the ultrasonic dispersion time is 1 to 2 h.

9. The method for preparing the MXene-SS / SF composite material according to claim 1, characterized in that: In step 2, when SS solution and SF solution are added to the MXene nanosheet dispersion, the mass parameter relationship between the MXene nanosheet dispersion, SS solution and SF solution is 7:1:2; during mixed self-assembly, after stirring at room temperature for 4 to 5 hours, ultrasonication for 1 to 2 hours is performed to obtain a MXene-SS / SF composite material with a total solute concentration of 10 mg / mL.

10. Use of the MXene-SS / SF composite material according to any one of claims 1 to 3 as a humidity sensing layer in physical detection.

Citation Information

Patent Citations

  • Sensor based on MXene / silk fibroin material and preparation method and application thereof

    CN114076785A

  • Super-elastic and high-adsorbability MXene aerogel and preparation method thereof

    CN114797747A

  • Self-correcting wearable temperature and humidity sensing system and preparation method and application thereof

    CN116164789A

  • Silk fibroin-MXene sponge composite material as well as preparation method and application thereof

    CN119236174A

  • Compositions and methods related to 2 dimensional molecular composites

    US20190352430A1